2018
DOI: 10.3390/met8100847
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Strength Analysis and Fatigue Damage Evaluation of Roller Chain

Abstract: This paper deals with the roller chain commonly used for transmission of mechanical power on many kinds of industrial machinery, including conveyors, cars, motorcycles, bicycles, and so forth. It consists of a series of four components called a pin, a bush, a plate, and a roller, which are driven by a sprocket. To clarify the fatigue damage, in this paper, the finite element method (FEM) is applied to those components under three different types of states, that is, the press-fitting state, the static tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For the application of a combined axial as well as torsional load, a mechanical roller chain, as investigated in reference, 16 is fastened around laser cut teeth on the steel ring of the specimens. These are clamped onto the testing rig, which is mounted eccentrically onto the universal testing machine center in order to create a defined peeling angle of α = 10.0°.…”
Section: Evaluation Of the Component Strength For Different Joint Geo...mentioning
confidence: 99%
“…For the application of a combined axial as well as torsional load, a mechanical roller chain, as investigated in reference, 16 is fastened around laser cut teeth on the steel ring of the specimens. These are clamped onto the testing rig, which is mounted eccentrically onto the universal testing machine center in order to create a defined peeling angle of α = 10.0°.…”
Section: Evaluation Of the Component Strength For Different Joint Geo...mentioning
confidence: 99%
“…In the worst case, undesired phenomena such as “jumping over teeth,” “jumping off the chain” and sprocket wear are produced. Kim and Song (2020) and Saito et al (2018) used the finite element method to analyze the stress state of the roller chain. The results show that the maximum pressure occurs at the intersection of the outer chain plate and the bush, where the pin bends and deforms under the action of forces.…”
Section: Introductionmentioning
confidence: 99%
“…The research works on industrial chains have been few, far less than those on rolling element bearings or gears. Kim and Song 1 and Saito et al 2 simulated the force state of the roller chain by finite element method and found that the maximum pressure on the pin situated at the intersect point of the bush and outer chain plate. Tandler et al 3 found that the maximum wear depth of the pin occurs at the left and right ends of the profile by the finite element simulation of the automobile chains, which is in good agreement with the real wear of the chain.…”
Section: Introductionmentioning
confidence: 99%